Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1177/0969141314560386
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the burden of interval cancers in long-standing screening mammography programmes

Abstract: The value of the PICR is hugely influenced by which method is applied, whereas the ICR is calculated purely on data available within programmes. We find that the PICR, the establishing indicator for sensitivity, could preferably be replaced by the ICR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…breast radiologists, in accordance with European screening guidance. In population-based screening programs, the general assumption is that if the reference screening modality (FFDM) is replaced by a more sensitive modality (DBT+SM), there is an initial increase of CDR at the first round, followed by a reduction in the CDR in subsequent rounds (17). The purpose of our study was to evaluate the diagnostic accuracy of consecutive screening rounds from the Verona Pilot Study (4), for which, after a first round of imaging with DBT+SM, approximately half of the study participants underwent repeat screening with DBT+SM and the other half underwent repeat screening with FFDM.…”
Section: Key Resultsmentioning
confidence: 99%
“…breast radiologists, in accordance with European screening guidance. In population-based screening programs, the general assumption is that if the reference screening modality (FFDM) is replaced by a more sensitive modality (DBT+SM), there is an initial increase of CDR at the first round, followed by a reduction in the CDR in subsequent rounds (17). The purpose of our study was to evaluate the diagnostic accuracy of consecutive screening rounds from the Verona Pilot Study (4), for which, after a first round of imaging with DBT+SM, approximately half of the study participants underwent repeat screening with DBT+SM and the other half underwent repeat screening with FFDM.…”
Section: Key Resultsmentioning
confidence: 99%
“…However, of all women eligible to all 5 invitation rounds, only 65% participated in all rounds, which is significantly lower than the participation rate in any of the individual rounds. This finding could be problematic, as Andersen’s 2015 study found that continued regular adherence among individuals is needed for optimal protection [ 20 ].…”
Section: Discussionmentioning
confidence: 99%